The current and future use of imaging in urological robotic surgery: a survey of the European Association of Robotic Urological Surgeons. Issue 1 (4th June 2014) - Hughes‐Hallett, Archie; Mayer, Erik K.; Pratt, Philip; Mottrie, Alex; Darzi, Ara; Vale, Justin
Abstract Background With the development of novel augmented reality operating platforms the way surgeons utilise imaging as a real‐time adjunct to surgical technique is changing. Methods A questionnaire was distributed via the European Robotic Urological Society mailing list. The questionnaire had three themes: surgeon demographics, current use of imaging and potential uses of an augmented reality operating environment in robotic urological surgery. Results 117 of the 239 respondents (48.9%) were independently practising robotic surgeons. 74% of surgeons reported having imaging available in theatre for prostatectomy 97% for robotic partial nephrectomy and 95% cystectomy. 87% felt there was a role for augmented reality as a navigation tool in robotic surgery. Conclusions This survey has revealed the contemporary robotic surgeon to be comfortable in the use of imaging for intraoperative planning it also suggests that there is a desire for augmented reality platforms within the urological community. Copyright © 2014 John Wiley & Sons, Ltd.